IMPACTUL UTILIZĂRII TABLEI INTERACTIVE LA STUDIEREA CURSULUI UNIVERSITAR TEHNOLOGII INFORMAŢIONALE ŞI COMUNICAŢIONALE. AVANTAJE ŞI DEZAVANTAJE - Lidia POPOV (Moldova State University, 2019)
În articol este abordat impactul utilizării tablei interactive la studierea cursului universitar Tehnologii informaționale și comunicaționale de către viitorii specialiști în domeniul sociojuridic. De asemenea, sunt reflectate opiniile studenților referitor la tehnologia interactivă. Este făcută o analiză a unui sondaj sociologic în baza căruia sunt scoase în relief atât avantajele, cât și dezavantajele utilizării tablei interactive.   THE IMPACT OF THE USING OF THE INTERACTIVE WHITEBOARD DURING THE AT UNIVERSITY COURSE INFORMATION AND COMMUNICATION TECHNOLOGIES. ADVANTAGES AND DISADVANTAGES This article describes the impact of using the interactive whiteboard in studying the ICT course at university for future socio-legal specialists. It also reflects students' views on interactive information technology. An analysis of a sociological survey based on the advantages and disadvantages of using the interactive whiteboard is made.